Magnetic solid-phase extraction material, preparation method thereof and application of magnetic solid-phase extraction material in determination of fat-soluble vitamins by high performance liquid chromatography
By preparing a magnetic co -price organic skeleton (Fe3O4@COFS) with a regular shape and larger surface area as a magnetic solid -phase extraction material, the problem of irregular shapes and adsorption in the existing technologies has achieved efficient, realized, efficient, and efficient, and Sensitive fat -soluble vitamin extraction and detection.
Patent Information
- Application Number
- CN202411580534.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-01-28
AI Technical Summary
In the prior art, magnetic nano microsphere adsorbents have irregular shapes, small specific surface area, and small adsorption amounts, making it difficult to meet the needs of large-scale vitamin extraction.
A preparation method is used to disperse the Fe3O4-NH2 under the action of ultrasound to the 1,4-epoxy sixth rings, and it has 2-3 aromatic compounds with 2-3 aldehydes and four- (amino benzhenyl) methane methane methane methane methane. (TAM) reacts to form a magnetic covalent organic skeleton (Fe3O4@COFS) as a magnetic solid -phase extraction material.
The prepared magnetic solid -phase extraction materials are shape rules, the spherical shape is complete, with a large ratio area and stability, can effectively adsorb and enrich the fat -rich vitamins, reduce artificial operation, improve the detection efficiency, and can be repeatedly used.
Smart Images

Figure CN119368148A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of food detection, and specifically relates to a magnetic solid phase extraction material and a preparation method thereof, and an application of the magnetic solid phase extraction material in the determination of fat-soluble vitamins by high performance liquid chromatography. Background Art
[0002] The content of fat-soluble vitamins is an important indicator for evaluating the quality of dairy products. Commonly used methods for chromatographic detection of vitamins include protein precipitation, liquid-liquid extraction, and solid-phase extraction. At present, when extracting fat-soluble vitamins from dairy products, organic solvent extraction (liquid-liquid extraction) is often used. This method has the characteristics of low cost and simple operation. Its principle is to extract and purify samples by utilizing the different distribution coefficients of the components to be analyzed and the interfering impurities in the biological sample in two immiscible solvents. However, this method has poor ability to remove endogenous interferences. The components to be tested need to be subjected to high-speed vortex oscillation and long-term centrifugation in the centrifuge tube, which is time-consuming and requires manual operation. In addition, incomplete solid-liquid separation can easily cause chromatographic column blockage and instrument contamination. It is not suitable for large-scale high-throughput fat-soluble vitamin extraction, which limits its practical application.
[0003] The occurrence of solid phase extraction mainly depends on the distribution coefficient of the target analyte between the stationary phase and the mobile phase. Therefore, in solid phase extraction, the selection of adsorbent materials is a key factor. Compared with traditional solid phase extraction, magnetic solid phase extraction technology consumes less organic solvent when separating and enriching the components to be tested, and the adsorbent can be reused after treatment, which is green and environmentally friendly; a small amount of adsorbent can separate and enrich the components to be tested from the sample in a shorter time, without the need for solid phase extraction columns, thus avoiding the occurrence of problems such as long column passing process and column clogging, and simplifying the extraction procedure; due to the magnetic responsiveness of the adsorbent itself, under the action of the external magnetic field, the adsorbent enriched with the analyte can be quickly separated from the sample solution or suspension, thereby eliminating the operation steps such as centrifugation and filtration; because the adsorbent is nano-scale, has a high specific surface area, a high adsorption volume and can be chemically modified, the adsorbent has a very high selectivity for the analyte to be tested; and the whole process can also be used in conjunction with automation technology, so choosing a suitable organic skeleton can optimize the process of magnetic solid phase extraction.
[0004] Covalent organic frameworks have been applied to the adsorption of various organic and inorganic substances due to their structural diversity, adjustable pore size, and modifiable external surface. Magnetic nanoparticles modified with organic frameworks are now commonly used as adsorbents for magnetic solid phase extraction. However, the functional magnetic nanoparticles prepared in the prior art are often irregular in shape, small in specific surface area, and small in adsorption capacity, which are not suitable for large-scale vitamin extraction. Therefore, it is of great significance to develop a magnetic solid phase extraction adsorbent with regular shape, strong adsorption capacity, and large adsorption capacity, as well as a method for determining fat-soluble vitamins with simple experimental procedures, high sensitivity, and high extraction efficiency. Summary of the invention
[0005] The technical problem to be solved by the present invention is that the magnetic nano-microsphere adsorbent in the prior art has irregular shape, small specific surface area, small adsorption capacity and other problems. The present invention provides a functionalized magnetic nano-microsphere with simple experimental process, high sensitivity, high extraction efficiency and regular shape, a preparation method and an application in the determination of fat-soluble vitamins by high performance liquid chromatography.
[0006] The technical solution of the present invention is as follows: One of the purposes of the present invention is to provide a method for preparing a magnetic solid phase extraction material, the method comprising: S1: Under the action of ultrasound, Fe 3 O 4 -NH 2 dispersed in 1,4-dioxane to obtain a suspension solution; S2: adding an aromatic compound with 2-3 aldehyde groups to the suspension solution of S1, dispersing it evenly to obtain a mixed solution; S3: adding pure acetic acid dropwise to the mixed solution of S2 and dispersing evenly to obtain a mixed solution 1; S4: transferring the mixed solution 1 of S3 to a hydrothermal reactor, placing it in an oven for reaction, and after the reaction is completed, washing, separating and drying to obtain modified magnetic nanoparticles; S5: dissolving an aromatic compound having 2-3 aldehyde groups and tetrakis-(aminophenyl)methane (TAM) in 1,4-dioxane to obtain a mixed solution 2; S6: dissolving the modified magnetic nanoparticles obtained in S4 in 1,4-dioxane to obtain a mixed solution 3; S7: Mix the mixed solution 2 of S5 and the mixed solution 3 of S6, and disperse them uniformly to obtain a mixed solution 4; S8: adding the acetic acid aqueous solution dropwise to the mixed solution 4 of S7 and dispersing evenly to obtain a mixed solution 5; S9: The mixed solution 5 of S8 is transferred to a hydrothermal reactor and placed in an oven for reaction. After the reaction is completed, the mixed solution 5 is washed, filtered, replaced and dried to obtain a magnetic covalent organic framework (Fe 3 O 4 @COFs) is a magnetic solid phase extraction material.
[0007] It is further defined that the aromatic compound with 2-3 aldehyde groups in S2 and S5 is 2,6-dialdehyde-1,5-dihydroxynaphthalene (DHNDA), 4,4'-biphenyldicarboxaldehyde, 4,4-p-tetraphenyldicarboxaldehyde, 2,4,6-triformylphloroglucinol, 2,5-dihydroxy-1,4-benzenedicarboxylic aldehyde or 2,6-naphthalenedicarboxylic aldehyde, and the Fe in S1 is 3 O 4-NH 2 The ratio of aromatic compounds with 2-3 aldehyde groups in S2 is 100 mg: 0.04-0.08 mmol.
[0008] It is further defined that the dispersion time of S2 is 1-5 min; the dispersion time of S3 is 1-5 min; the temperature of the S4 oven is 100-150° C., and the reaction time is 0.5-3 h.
[0009] It is further defined that the ratio of the aromatic compound with 2-3 aldehyde groups of S5 and TAM to the magnetic nanoparticles modified with S6 is 0.04-0.1 mmol:0.02-0.04 mmol:20 mg.
[0010] It is further defined that the dispersion time of S7 is 1-5 min; the dispersion time of S8 is 1-5 min, the concentration of acetic acid water is 6 mol / L, and the volume is 1.5 mL.
[0011] It is further defined that the temperature of the oven in S9 is 100-150° C. and the reaction time is 48-100 h.
[0012] A second object of the present invention is to provide a magnetic solid phase extraction material prepared by the above preparation method.
[0013] The third object of the present invention is to provide an application of the magnetic solid phase extraction material in the determination of fat-soluble vitamins by high performance liquid chromatography.
[0014] A fourth object of the present invention is to provide a high performance liquid chromatography detection method for fat-soluble vitamins based on magnetic solid phase extraction, comprising the following steps: S1: Pre-treat the fat-soluble vitamin samples to be tested; S2: using the magnetic solid phase extraction material as an adsorbent, the fat-soluble vitamin sample to be tested after pretreatment is first adsorbed and then extracted, the supernatant is discarded, and then eluted, concentrated, and then filtered using a 0.22 μm organic filter membrane to obtain a filtrate to be tested; S3: Detect the filtrate using high performance liquid chromatography.
[0015] It is further defined that in step S2 of the above detection method, the amount of adsorbent used is 4-6 mg, the adsorption time is 25-40 min, the temperature is 45°C, the eluent is methanol, the eluent volume is 6-8 mL, the extraction time is 8-12 min, and the concentration is 6-30 times.
[0016] It is further defined that in step S2 of the detection method, the amount of adsorbent used is 5 mg, the adsorption time is 30 min, the volume of the eluent is 6 mL and the elution is divided into two equal portions, and the extraction time is 10 min.
[0017] Compared with the prior art, the specific advantages of the present invention are as follows: (1) The advantages of the present invention are: the determination method of the present invention is based on Fe 3 O 4 @COFs is a magnetic solid phase extraction material. A new magnetic solid phase extraction-high performance liquid chromatography detection method was established to achieve quantitative detection of fat-soluble vitamins in dairy products. The material has a regular shape and a complete sphere. It has the stability of a covalent organic skeleton and a large specific surface area. It also has the characteristics of easy separation and reusability of magnetic materials. It reduces manual participation when using high performance liquid chromatography to determine fat-soluble vitamins, which is conducive to the development of semi-automatic and automated detection and can effectively reduce economic costs. This method also provides a reference for efficient and rapid detection of other nutrients in dairy products.
[0018] (2) The present invention uses Fe 3 O 4 @COFs was used as an adsorbent for magnetic solid phase extraction, and combined with liquid chromatography to detect fat-soluble vitamins in liquid samples. The magnetic composite material was characterized by Fourier transform infrared spectroscopy, scanning electron microscopy, and hysteresis loop technology. The factors such as adsorbent dosage, adsorption time, eluent type, eluent volume, and extraction time in the magnetic solid phase extraction process were optimized. Under the optimal experimental conditions, vitamin A had a good linear relationship in the range of 1 to 20 mg / L (R 2 =0.9998), the standard deviation was less than 0.45%, the detection limit and quantification limit were 20.0ng / mL and 55.0ng / mL respectively, and the adsorption rate could reach 95%; Vitamin D 3 The linear relationship is good in the range of 1 to 20 mg / L (R 2 =0.9998), the standard deviation was less than 0.38%, the detection limit and quantification limit were 50.0 ng / mL and 150.0 ng / mL respectively, the adsorption rate could reach 97%, and the linear relationship of vitamin E was good in the range of 2-20 mg / L (R 2 =0.9998), the standard deviation was less than 0.5%, the detection limit and quantification limit were 40.0 ng / mL and 100.0 ng / mL respectively, and the adsorption rate could reach 93%.
[0019] (3) The new magnetic solid phase extraction high performance liquid chromatography detection method established by the present invention has an enrichment effect and can be used for quantitative analysis of fat-soluble vitamins in infant formula milk powder, liquid milk and breast milk, providing new technical support for the quantitative detection of fat-soluble vitamins. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 TAM, DHNDA, Fe 3 O 4 @NH2 and Fe 3 O 4 @Infrared spectrum of COFs; Figure 2 A is Example 1Fe 3 O 4 -NH 2 Scanning electron microscope images of Figure 2 B is Example 1Fe 3 O 4 @SEM images of COFs; Figure 3 A is Fe of Example 1 3 O 4 -NH 2 and Fe 3 O 4 @Hysteresis loop of COFs; Figure 3 B is Example 1Fe 3 O 4 @COFs dispersion and separation process; Figure 4 is the Fe of Example 1 3 O 4 -NH 2 and Fe 3 O 4 @Elemental analysis diagram of COFs; Figure 5 is Fe in Example 1 3 O 4 @The effect of COFs addition on adsorption efficiency; Figure 6 The adsorption time of Fe in Example 1 3 O 4 @The influence of COFs adsorption efficiency; Figure 7 The effect of adsorption temperature on Fe 3 O 4 @The influence of COFs adsorption efficiency; Figure 8 The effect of solvent type on the Fe 3 O 4 @The influence of COFs extraction efficiency; Fig. 9 The amount of solvent added to the Fe 3 O 4 @The influence of COFs extraction efficiency; Fig.10 The Fe of Example 1 3 O 4 @COFs reusability test; Fig.11A is Fe of Example 1 3 O 4 @COFs adsorption efficiency test in mixed fat-soluble vitamin solutions with different initial concentrations, Fig.11 B is Fe 3 O 4 @COFs adsorption efficiency test in single fat-soluble vitamin solutions with different initial concentrations; Fig.12 It is the chromatogram of Example 2 and Comparative Example 1; Fig.13 It is the chromatogram of Example 3 and Comparative Example 2; Fig.14 It is the chromatogram of Example 4 and Comparative Example 3. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0022] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0023] The terms "comprising," "including," "having," "containing," or any other variations thereof, as used in the following examples, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus comprising the listed elements is not necessarily limited to only those elements, but may include other elements not expressly listed or inherent to such composition, step, method, article, or apparatus.
[0024] The endpoints and any values of the ranges disclosed in the invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article.
[0025] The following are the materials used in the examples: Fe 3 O 4 -NH 2 Nanoparticles: BeyoMag™ Amine Magnetic Beads (amino magnetic beads, 200 nm); BeyoMag™ Amine Magnetic Beads.
[0026] Breast milk: human female volunteers.
[0027] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0028] Embodiment 1: Under the action of ultrasound, Fe 3 O 4 -NH 2 Nanoparticles (100 mg) were dispersed in 10 mL of 1,4-dioxane. DHNDA (0.075 mmol) was then added to the suspension, ultrasonicated for 1 min, acetic acid (150 μL) was added dropwise to the mixture, and the mixture was ultrasonicated for 3 min. Finally, the suspension was transferred to a polytetrafluoroethylene-lined hydrothermal reactor, placed in an oven, and reacted at 120 ° C for 1 h. After the reaction, it was rinsed with 1,4-dioxane and methanol in turn, separated by a magnet, and dried in a vacuum oven at 50 ° C for 12 h to obtain 2,6-dialdehyde-1,5-dihydroxynaphthalene modified magnetic nanoparticles (Fe 3 O 4 -DHNDA).
[0029] The Fe synthesized above 3 O 4 -DHNDA (20 mg) was dispersed in 1,4-dioxane (5 mL), and then mixed with DHNDA (0.075 mmol) and TAM (0.0375 mmol) dissolved in 1,4-dioxane (8 mL), and ultrasonicated for 1 min. An aqueous solution of acetic acid (6 M, 1.5 mL) was added dropwise to the above mixture, and ultrasonicated for 3 min. The solution was transferred to a polytetrafluoroethylene-lined hydrothermal reactor, placed in an oven, and reacted at 120 ° C for 72 h. It was washed with N, N-dimethylformamide (DMF), 1,4-dioxane, and methanol to remove unreacted monomers, and an orange-red solid was obtained by centrifugation and filtration, and then replaced with methanol solvent for 24 h. Methanol was replaced every 4 h during the replacement period, and dried overnight in a vacuum oven at 80 ° C to obtain Fe 3 O 4 @COFs.
[0030] Sample pretreatment: 3 mL of raw milk without detectable fat-soluble vitamins was mixed with phosphate buffer solution (0.5 mL, pH 7.2) and ascorbic acid-ethanol solution (5 mL, 0.5%). After vortexing for 1 min, the sample was centrifuged at 1792×grpm and 20°C for 10 min. The supernatant was filtered with a 0.45 μm filter membrane to obtain a blank matrix. The blank matrix was used to prepare vitamin A, D and E solutions, respectively, so that the concentrations of vitamin A, D and E solutions were all 20 mg / L. These three solutions with added fat-soluble vitamins were used for experimental testing.
[0031] Magnetic solid phase extraction: weigh 5 mg of Fe 3 O 4 @COFs, add 1 mL of the spiked test solution and shake it in a constant temperature shaker for 30 minutes to allow the fat-soluble vitamins to be fully adsorbed. Then use a magnet for magnetic separation, discard the supernatant, transfer 6 mL of methanol and elute it twice on average. After elution for 10 minutes, use a magnet for liquid-solid separation, take the separated supernatant for nitrogen blowing, re-dissolve it in 1 mL of methanol, and pass the re-dissolved solution through a 0.22 μm organic filter membrane.
[0032] High-performance liquid chromatography analysis: The eluent was analyzed by high-performance liquid chromatography using a high-performance liquid chromatography diode array detector to determine the fat-soluble vitamins in the sample. The chromatographic column was Aglient C18 (250 mm × 4.6 mm, 5 μm); the mobile phase was methanol, and isocratic elution was performed; the UV detection wavelengths were: 325 nm, 265 nm, and 293 nm; the flow rate was: 1.0 mL / min; the column temperature was: 30 °C; the injection volume was: 10 μL.
[0033] Embodiment 2: The magnetic solid phase extraction-high performance liquid chromatography analysis method established by the method of the present invention is used for the quantitative detection of fat-soluble vitamins in infant formula milk powder: Preparation of Fe 3 O 4 @COFs are the same as in Example 1; Sample pretreatment: 3 mL (1 g of milk powder fully dissolved in 5 mL of deionized water) of infant formula milk powder (Yili Zhenhu Stage 1) after reconstitution was mixed with phosphate buffer solution (0.5 mL, pH 7.2) and ascorbic acid-ethanol solution (5 mL, 0.5%). After vortexing for 1 min, the sample was centrifuged at 1792 × grpm and 20 °C for 10 min, and the supernatant was filtered with a 0.45 μm filter membrane. The magnetic solid phase extraction method is different from that of Example 1 in that 0.5 mL of methanol is used for redissolution after nitrogen blowing, and the remaining steps are the same as those of Example 1; The HPLC analysis was the same as that in Example 1.
[0034] Embodiment 3: The magnetic solid phase extraction-high performance liquid chromatography analysis method established by the method of the present invention is used for the quantitative detection of fat-soluble vitamins in infant liquid milk: Preparation of Fe 3 O 4 @COFs are the same as in Example 1.
[0035] Sample pretreatment: 3 mL of Nestlé infant formula liquid milk was mixed with phosphate buffer solution (0.5 mL, pH 7.2) and ascorbic acid-ethanol solution (5 mL, 0.5%). After vortexing for 1 min, the sample was centrifuged at 1792 × grpm and 20 °C for 10 min, and the supernatant was filtered with a 0.45 nm filter membrane.
[0036] The magnetic solid phase extraction method is different from that of Example 1 in that 0.5 mL of methanol is used for redissolution after nitrogen blowing, and the remaining steps are the same as those of Example 1; The HPLC analysis was the same as that in Example 1.
[0037] Embodiment 4: The magnetic solid phase extraction-high performance liquid chromatography analysis method established by the method of the present invention is used for the quantitative detection of fat-soluble vitamins in infant liquid milk: Preparation of Fe 3 O 4 @COFs are the same as in Example 1.
[0038] Sample pretreatment: 3 mL of breast milk was mixed with phosphate buffer solution (0.5 mL, pH 7.2) and ascorbic acid-ethanol solution (5 mL, 0.5%). After vortexing for 1 min, the sample was centrifuged at 1792 × grpm and 20 °C for 10 min, and the supernatant was filtered with a 0.45 nm filter membrane.
[0039] The magnetic solid phase extraction method is different from that of Example 1 in that 0.5 mL of methanol is used for redissolution after nitrogen blowing, and the remaining steps are the same as those of Example 1; The HPLC analysis was the same as that in Example 1.
[0040] Comparative Example 1: The sample pretreatment was the same as that in Example 2, except that the supernatant was directly taken out without undergoing magnetic solid phase extraction and nitrogen purged, and then re-dissolved in 0.5 mL of methanol. The HPLC analysis was then the same as that in Example 2.
[0041] Comparative Example 2: The sample pretreatment was the same as that in Example 3, except that the supernatant was directly taken out without undergoing magnetic solid phase extraction, nitrogen was blown, and then re-dissolved in 0.5 mL of methanol. The HPLC analysis was then the same as that in Example 3.
[0042] Comparative Example 3: The sample pretreatment was the same as that in Example 4, except that the supernatant was directly taken out without undergoing magnetic solid phase extraction, nitrogen was blown, and then re-dissolved in 0.5 mL of methanol. The HPLC analysis was then the same as that in Example 4.
[0043] Figure 1 The infrared spectrum of Example 1 is as follows: Figure 1 As shown, TAM is at 3395 cm -1 The amino group (-NH 2 ) characteristic peak and DHNDA at 1640cm -1 The C=O characteristic peak of COFs disappeared, proving the successful preparation of COFs. -1 A new C=N bond characteristic absorption peak appears at 1507cm -1 and 1407cm -1 The C=C stretching vibration absorption peak attributed to the aromatic ring is 1291m -1 The absorption peaks at 3440 cm-1 were attributed to the CN stretching vibration, indicating the successful synthesis of COFs through the reversible Schiff base reaction and the irreversible enol-keto tautomerization. -1 The broad absorption peak at 100 nm confirmed the introduction of hydroxyl groups. 3 O 4 -NH 2 The 589 cm -1 The bands near are attributed to the stretching vibration of Fe-O-Fe bonds. 3 O 4 In the infrared spectrum of @COFs, all characteristic peaks of COFs are present, which indicates that the chemical structure of COFs remains intact. After the magnetic nanoparticles are composited with the matrix, the C=C (1507 cm -1 ) and C=N(1606cm -1 ) The stretching vibration peaks still exist, ensuring that the magnetic loading does not destroy the basic COFs structure.
[0044] Figure 2 is the Fe of Example 1 3 O 4 -NH 2 and Fe 3 O 4 @SEM images of COFs; Figure 2 As shown, Fe 3 O 4 -NH 2 It has a spherical structure and a rough surface morphology. 3 O 4 The morphology of @COFs retains Fe 3 O4 -NH 2 The spherical structure and surface roughness of the spheres, and the increase in spherical diameter, indicate that the material was successfully synthesized, and the synthesis of Fe 3 O 4 @COFs have complete spherical shape, rough surface and large specific surface area.
[0045] Figure 3 The Fe of Example 1 3 O 4 -NH 2 and Fe 3 O 4 @COFs hysteresis loop diagram: Figure 3 As shown in A, it can be seen from the figure that the Fe 3 O 4 @COFs composites have typical superparamagnetism, Fe 3 O 4 -NH 2 and Fe 3 O 4 The saturation magnetization values of @COFs are 40.2emu / g and 21.2emu / g, respectively. 3 O 4 -NH 2 Compared with magnetic materials, magnetic covalent organic framework Fe 3 O 4 The saturation magnetization values of @COFs are slightly reduced, but Figure 3 It can be seen that Fe 3 O 4 The magnetization intensity of @COFs meets the requirements of rapid separation in experiments.
[0046] Figure 4 The Fe of Example 1 3 O 4 -NH 2 and Fe 3 O 4 @COFs elemental analysis diagram: from Figure 4 It can be seen that Fe 3 O 4 -NH 2 The C and N elements contained in the magnetic carrier are relatively low, mainly derived from 3-aminopropyltriethoxysilane, which are 1.16% and 0.31% respectively. When the covalent organic framework is formed on the surface of the magnetic carrier, the C and N contents increase significantly, reaching 28.64% and 2.93% respectively. This is because the building blocks of COFs contain C and N elements, which further explains the Fe 3 O 4 Successful preparation of @COFs.
[0047] Figure 5 The Fe of Example 1 3 O 4 @Effect of COFs addition on adsorption efficiency: The amount of adsorbent is the key factor affecting the adsorption capacity. The experimental conditions are: at 25°C, the volume of the adsorption solution is 1 mL, the concentrations of vitamin A, vitamin D and vitamin E are all 20.0 mg / L, the oscillation speed is 300 r / min, and the time is 30 min. 3 O 4 @COFs dosage of 2-8 mg was tested on the adsorption capacity. The results are as follows Figure 5 As shown in the figure, the adsorption capacity of fat-soluble vitamins increases with the increase of adsorbent dosage. The more adsorbent dosage is used, the more adsorption sites can be provided. When the adsorbent dosage is greater than 5 mg, the adsorption capacity reaches saturation. Therefore, the optimal dosage of the adsorbent is 5 mg.
[0048] Figure 6 is the adsorption time for Fe in Example 1 3 O 4 @COFs adsorption efficiency: This paper investigates the effect of Fe 3 O 4 @The effect of COFs adsorption time on the extraction efficiency of fat-soluble vitamins. Experimental conditions: at 25°C, the volume of the adsorption solution was 1 mL, the amount of adsorbent was 5 mg, the concentrations of vitamin A, vitamin D and vitamin E were all 20.0 mg / L, the oscillation speed was 300 r / min, and the time was 30 min. The results are shown in Figure 6 As shown in the figure, within 15 minutes, the adsorption capacity increases rapidly, and within 15-25 minutes, the adsorption capacity increases slowly with time, reaching 85% of the saturated adsorption capacity, and the adsorption saturation state is reached at 30 minutes. This is because in the initial stage, Fe 3 O 4 @COFs provides a large number of adsorption sites. The concentration of fat-soluble vitamins in the solution is high and the adsorption rate is fast. After 15 minutes, Fe 3 O 4 @COFs have fewer adsorption sites, and the concentration of fat-soluble vitamins in the solution also decreases, resulting in a slower adsorption rate.
[0049] Figure 7 is the effect of adsorption temperature on Fe 3 O 4 @Influence of COFs adsorption efficiency: This paper investigates the adsorption efficiency of Fe 3 O 4@The effect of COFs on the adsorption efficiency of fat-soluble vitamins. Experimental conditions: adsorption solution volume 1mL, adsorbent dosage 5mg, vitamin A, vitamin D and vitamin E concentrations 20.0mg / L, oscillation speed 300r / min, time 30min. The results are as follows Figure 7 As shown, at 45℃, Fe 3 O 4 @COFs can achieve an adsorption efficiency of 95% for fat-soluble vitamins. This is because high temperature intensifies the collision between molecules, which makes Fe 3 O 4 @COFs has improved the adsorption efficiency of fat-soluble vitamins. However, since fat-soluble vitamins will decompose at high temperatures, the selected extraction temperature should not be too high, so 45°C is selected as the optimal extraction temperature.
[0050] Figure 8 The effect of solvent type on the Fe 3 O 4 @COFs extraction efficiency: Fe 3 O 4 @COFs’ adsorption of fat-soluble vitamins mainly relies on π-π interactions and hydrogen bonds. The purpose of exploring the types of solvents is to improve the efficiency of eluting fat-soluble vitamins. Experimental conditions: at 45°C, the volume of the adsorption solution is 1mL, the amount of adsorbent is 5mg, the concentrations of vitamin A, vitamin D and vitamin E are all 20.0mg / L, the oscillation speed is 300r / min, the time is 30min, and the elution time is 10min. The present invention investigates the elution ability of six organic solvents, including methanol, acetonitrile, acetone, n-hexane, and acetonitrile (0.1% formic acid), on fat-soluble vitamins. Figure 8 As shown, methanol has the strongest elution effect among the six solvents. This is because methanol itself is a highly polar substance, which can destroy the hydrogen bonding force between vitamins and adsorbents, thereby achieving the effect of efficiently eluting fat-soluble vitamins.
[0051] Fig. 9 The amount of solvent added to the Fe 3 O 4 @The influence of COFs extraction efficiency: The present invention also investigates the effect of eluent volume on the elution efficiency of fat-soluble vitamins. When the sample volume is constant, the smaller the eluent volume, the greater the enrichment multiple. Experimental conditions: at 45°C, the adsorption solution volume is 1mL, the adsorbent dosage is 5mg, the concentrations of vitamin A, vitamin D and vitamin E are all 20.0mg / L and there is only one fat-soluble vitamin, the oscillation speed is 300r / min, the time is 30min, methanol is selected as the elution solvent, and the elution time is 10min. The results are as follows Fig. 9As shown in the figure, the recovery rate of fat-soluble vitamins increases with the increase of eluent volume. When the volume is greater than 6 mL, the recovery rate is basically stable. Therefore, 6 mL of methanol with the best elution effect is selected as the eluent volume, and the elution is divided into two times, 3 mL each time.
[0052] Fig.10 The Fe of Example 1 3 O 4 @COFs reusability test: Reusability is an important indicator for evaluating the performance of adsorbents. High-quality adsorbents can not only reduce the cost of synthesis, but also reduce pollution to the environment. The present invention carried out 5 adsorption-desorption cycle experiments according to the process of "magnetic solid phase extraction" to evaluate the effect of its repeatability on the adsorption performance of fat-soluble vitamins. Experimental conditions: at 45°C, the volume of the adsorption solution was 1mL, the amount of adsorbent was 5mg, the concentrations of vitamin A, vitamin D and vitamin E were all 20.0mg / L, the oscillation speed was 300r / min, the time was 30min, 6mL of methanol was selected as the elution solvent and eluted twice, 3mL each time, and the elution time was 10min. The results are as follows Fig.10 As shown in Figure 2, the adsorption of fat-soluble vitamins decreased slightly with the increase in the number of cycles, which may be due to the increase in Fe 3 O 4 The fat-soluble vitamins adsorbed on the @COFs adsorbent were not completely eluted, resulting in a slight decrease in the number of effective adsorption sites. However, after repeating the experiment 5 times, the adsorption rate of fat-soluble vitamins could still reach 90%, indicating that Fe 3 O 4 @COFs have good recyclability.
[0053] Fig.11 A is Fe of Example 1 3 O 4 @COFs adsorption efficiency test in mixed fat-soluble vitamin solutions with different initial concentrations, Fig.11 B is the adsorption efficiency test in single fat-soluble vitamin solutions with different initial concentrations. The experiment is to explore whether the three fat-soluble vitamins in the mixed solution will interfere with each other. Fig.11 Experimental conditions of A: at 45°C, the mixed fat-soluble vitamin solution is a mixture of vitamin A, vitamin D and vitamin E. The concentrations of the three mixed vitamins are the same, and there are 6 concentrations in total, namely 8.0, 12.0, 16.0, 20.0, 24.0 and 30.0 mg / L. The volume of the adsorption solution is 1 mL, the amount of adsorbent is 5 mg, the oscillation speed is 300 r / min, the time is 30 min, 6 mL of methanol is selected as the elution solvent and eluted twice, 3 mL each time, and the elution time is 10 min. Fig.11Experimental conditions of B: at 45°C, the single fat-soluble vitamin solution consists of vitamin A, vitamin D and vitamin E. The three vitamins are divided into 6 concentrations, namely 8.0, 12.0, 16.0, 20.0, 24.0 and 30.0 mg / L, the adsorption solution volume is 1 mL, the adsorbent dosage is 5 mg, the oscillation speed is 300 r / min, the time is 30 min, 6 mL of methanol is selected as the elution solvent and eluted twice, 3 mL each time, and the elution time is 10 min.
[0054] The results showed that there was almost no interference between fat-soluble vitamins in the mixed solution. Fig.11 A and Fig.11 As the concentration of fat-soluble vitamins increases, Fe 3 O 4 The adsorption efficiency of @COFs first increased and then decreased. This is because when the concentration of fat-soluble vitamins is low, Fe 3 O 4 @COFs surface adsorption sites are not fully occupied. When the concentration is low, fat-soluble vitamins can be almost fully adsorbed. 3 O 4 @COFs adsorption efficiency is very high, but as the concentration increases, Fe 3 O 4 @The adsorption sites on the surface of COFs are all occupied and can no longer adsorb fat-soluble vitamins, so the adsorption efficiency will be reduced.
[0055] A series of fat-soluble vitamin calibration solutions were prepared with mass concentrations of 20.0, 10.0, 5.0, 2.0, and 1.0 mg / L. Magnetic solid phase extraction-high performance liquid chromatography analysis was performed under the optimal experimental conditions tested above. A standard curve was established and linear regression was performed. Vitamin A: y=33.111x-13.372, vitamin D 3 :y=26.282x-19.444, Vitamin E:y=2.9042x-4.4895.
[0056] The detection limit and quantification limit were calculated based on 3-fold and 10-fold signal-to-noise ratios (S / N). The detection limit and quantification limit of vitamin A were 20.0 ng / mL and 55.0 ng / mL, respectively, and the detection limit and quantification limit of vitamin D were 20.0 ng / mL and 55.0 ng / mL, respectively. 3 The detection limit and quantification limit of are 50.0ng / mL and 150.0ng / mL respectively, and the detection limit and quantification limit of vitamin E are 40.0ng / mL and 100.0ng / mL respectively. The detection limit and quantification limit of this method are relatively low.
[0057] By continuously measuring 20.0 mg / L fat-soluble vitamin standard solution for 5 times, the relative standard deviation was less than 0.5%. This method has good reproducibility and can be applied to the quantitative detection of fat-soluble vitamins.
[0058] Fig.12 It is the chromatogram of Example 2 and Comparative Example 1. The result is as follows Fig.12 As shown, from Fig.12 We can see that after magnetic solid phase extraction, the target peak becomes significantly larger, proving that the magnetic solid phase extraction-high performance liquid chromatography analysis method established in this experiment can be applied to the quantitative analysis of fat-soluble vitamins in infant formula milk powder.
[0059] Fig.13 It is the chromatogram of embodiment 3 and comparative example 2. The result is as follows Fig.13 As shown, from Fig.13 We can see that the target peak becomes significantly larger, proving that the magnetic solid phase extraction-high performance liquid chromatography analysis method established in this experiment can be applied to the quantitative analysis of fat-soluble vitamins in infant liquid milk.
[0060] Fig.14 It is the chromatogram of Example 4 and Comparative Example 3. The result is as follows Fig.14 As shown, from Fig.14 We can see that the target peak becomes significantly larger, proving that the magnetic solid phase extraction-high performance liquid chromatography analysis method established in this experiment can be applied to the quantitative analysis of fat-soluble vitamins in breast milk. Fig.12 , Fig.13 and Fig.14 All these indicate that this method has an enrichment effect and provides new technical support for the detection of fat-soluble vitamins.
[0061] Through the above test, it is verified that the Fe 3 O 4 @COFs is a magnetic solid phase extraction material. The magnetic solid phase extraction-high performance liquid chromatography analysis method established realizes the quantitative detection of fat-soluble vitamins in dairy products. 3 O 4 @COFs materials have regular and complete spherical shapes, good stability and large specific surface area of covalent organic frameworks, and are easy to separate and reusable as magnetic materials, which effectively reduces economic costs. The method of the present invention also provides a reference for the efficient and rapid detection of other nutrients in samples.
[0062] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a magnetic solid phase extraction material, characterized in that: The method: S1: Under the action of ultrasound, Fe3O4-NH2 is dispersed in 1,4-dioxane to obtain a suspension solution; S2: adding an aromatic compound with 2-3 aldehyde groups to the suspension solution of S1, dispersing it evenly to obtain a mixed solution; S3: adding pure acetic acid dropwise to the mixed solution of S2 and dispersing evenly to obtain a mixed solution 1; S4: transferring the mixed solution 1 of S3 to a hydrothermal reactor, placing it in an oven for reaction, and after the reaction is completed, washing, separating and drying to obtain modified magnetic nanoparticles; S5: dissolving an aromatic compound having 2-3 aldehyde groups and tetrakis-(aminophenyl)methane in 1,4-dioxane to obtain a mixed solution 2; S6: dissolving the modified magnetic nanoparticles obtained in S4 in 1,4-dioxane to obtain a mixed solution 3; S7: Mix the mixed solution 2 of S5 and the mixed solution 3 of S6, and disperse them uniformly to obtain a mixed solution 4; S8: adding the acetic acid aqueous solution dropwise to the mixed solution 4 of S7 and dispersing evenly to obtain a mixed solution 5; S9: The mixed solution 5 of S8 is transferred to a hydrothermal reactor and placed in an oven for reaction. After the reaction is completed, the mixed solution 5 is washed, filtered, replaced and dried to obtain a magnetic covalent organic framework as a magnetic solid phase extraction material.
2. The preparation method according to claim 1, characterized in that: The aromatic compounds with 2-3 aldehyde groups in S2 and S5 are 2,6-dialdehyde-1,5-dihydroxynaphthalene, 4,4'-biphenyldicarboxaldehyde, 4,4-p-tetraphenyldicarboxaldehyde, 2,4,6-triformylphloroglucinol, 2,5-dihydroxy-1,4-benzenedicarboxylic acid aldehyde or 2,6-naphthalenedicarboxylic acid aldehyde, and the ratio of Fe3O4-NH2 in S1 to the aromatic compounds with 2-3 aldehyde groups in S2 is 100mg:0.04-0.08mmol.
3. The preparation method according to claim 1, characterized in that: The dispersion time of S2 is 1-5min; the dispersion time of S3 is 1-5min; the temperature of the oven of S4 is 100-150℃, and the reaction time is 0.5-3h.
4. The preparation method according to claim 1, characterized in that: The ratio of S5's aromatic compound with 2-3 aldehyde groups and tetrakis-(aminophenyl)methane to S6-modified magnetic nanoparticles is 0.04-0.1mmol:0.02-0.04mmol:20mg.
5. The preparation method according to claim 1, characterized in that: The dispersion time of S7 is 1-5 min; the dispersion time of S8 is 1-5 min, the concentration of acetic acid water is 6 mol / L, and the volume is 1.5 mL.
6. The preparation method according to claim 1, characterized in that: The temperature of the oven of S9 is 100-150°C, and the reaction time is 48-100h.
7. A magnetic solid phase extraction material, characterized in that: The magnetic solid phase extraction material is prepared by the preparation method according to any one of claims 1 to 7.
8. Use of the magnetic solid phase extraction material according to claim 7 in the determination of fat-soluble vitamins by high performance liquid chromatography.
9. A liquid chromatography detection method for fat-soluble vitamins based on magnetic solid phase extraction, characterized in that: The following steps are involved: S1: Pre-treat the fat-soluble vitamin samples to be tested; S2: using the magnetic solid phase extraction material of claim 7 as an adsorbent, first adsorbing and then extracting the fat-soluble vitamin sample to be tested after pretreatment, discarding the supernatant, eluting, concentrating, and then filtering with a 0.22 μm organic filter membrane to obtain a filtrate to be tested; S3: Detect the filtrate using high performance liquid chromatography.
10. The detection method according to claim 9, characterized in that: In step S2, the amount of adsorbent used is 4-6 mg, the adsorption time is 25-40 min, the temperature is 45° C., the eluent is methanol, the eluent volume is 6-8 mL, the extraction time is 8-12 min, and the concentration is 6-30 times.